2017
DOI: 10.1108/ijcma-02-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Religious motivation, nepotism and conflict management in Jordan

Abstract: Purpose - The purpose of this research paper is to investigate the role of individual and cultural differences, specifically religious motivation and attitudes toward nepotism, in the selection of conflict management styles (obliging, avoiding, forcing, integrating, and compromising), in the Middle-Eastern context.\ud Design/methodology/approach - The research surveyed a sample of 588 individuals (both Muslims and Christians), representative of the Jordanian population. Data were analyzed through multiple ANOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 83 publications
0
13
0
2
Order By: Relevance
“…Employee age may be another factor that is important for the manifestation of nepotism and favouritism. The study conducted in Jordan has demonstrated that professed religion influenced nepotism, and age did not matter [64]. However, the research carried out in Turkey has shown that age mattered to friends' patronage in the working environment [65].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Employee age may be another factor that is important for the manifestation of nepotism and favouritism. The study conducted in Jordan has demonstrated that professed religion influenced nepotism, and age did not matter [64]. However, the research carried out in Turkey has shown that age mattered to friends' patronage in the working environment [65].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Jordan is a small, developing country without access to the natural resource base that many other MENA region countries enjoy, but which has an enviable human capital base. It is also characterized by high social cohesion and a collectivistic approach to problem-solving (Caputo, 2018). The problem for youth in Jordan is not a lack of educational opportunities, but a lack of jobs adequate to provide a living wage without leaving the country for employment abroad (Bills, 2015).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Finally, we also note that in the Arab world, there is a strongly patriarchal and paternalist approach, especially towards female family members (Caputo, 2018; Mehtap et al, 2019; Petrolo et al, 2018). This situation implies that where women are more emancipated and where the business world is more open to the presence of women, as evident in stable countries such as Jordan, strong emotional support from the family may be perceived by the female entrepreneur as a lack of confidence in her abilities.…”
Section: Theoretical Backgroundmentioning
confidence: 77%
“…In addition to the family-business nexus, it also is important to understand the significance of the general context for studies on women’s entrepreneurship in general and specifically in Arab countries (Dana and Dana, 2005). Because a conservative culture and a patriarchal approach are deeply socially-embedded in this part of the world (Caputo, 2018; Dana, 2000; Petrolo et al, 2018), female entrepreneurs face stronger barriers compared to their colleagues elsewhere (Dana et al, 2018; Kolvereid et al, 1993). While Islam per se is not a constraining factor for women’s participation in economic activity, social customs and tribal traditions may inhibit entrepreneurial attitudes towards women in the Arab world.…”
Section: Theoretical Backgroundmentioning
confidence: 99%